Delirium in children – new research directions (Journal of Medical Science, 2021)
One of the problems associated with a patient’s stay in the hospital and the procedures they undergo is delirium, the occurrence of which is associated with numerous complications, longer stay in the ward, higher risk of death and increased healthcare costs. Scientists are continuing to search for effective methods to minimise the risk of its occurrence, as well as to develop effective therapeutic procedures. One such area of the research is the identification of delirium biomarkers, which would allow further PK/PD (pharmacokinetic/pharmacodynamic) modelling. This article focuses on the emergence delirium, which occurs in patients recovering from general anaesthesia.